Perceived shared decision making and satisfaction with care among children and adolescents with special healthcare needs and their parents: Cross-sectional evidence from the PART-CHILD Study - Nisius, Katja; Hoffmann, Dorle; Görig, Tatiana; Georg, Sabine; Krug, Katja; Bock, Freia de; Eichinger, Michael (Patient education and counseling, 2024)
Objectives - To compare shared decision making (SDM) and satisfaction with care (SWC), an indicator of care quality, between children with special healthcare needs (CSHCN) and parents and to assess the association between SDM and SWC in both groups. - Methods - We recruited CSHCN ≥ 7 years and parents from 15 outpatient facilities that completed a paper questionnaire assessing SDM (highest vs. lower levels of SDM) and SWC. Differences in SDM and SWC were assessed with McNemar and paired t-tests. We used adjusted linear mixed models to investigate cross-sectional associations between SDM and SWC. - Results - Based on data from 275 CSHCN and 858 parents, 39% and 64% of CSHCN and parents reported the highest level of SDM (p < 0.0001). No difference in SWC was observed (p = 0.36). Perceived SDM was associated with SWC in both groups (both p < 0.0001). - Conclusion - Associations between SDM and SWC reinforce the role of SDM for care quality. Large proportions of CSHCN and parents reporting suboptimal levels of SDM highlight the need for effective programs to promote SDM in the target population. - Practice implications - Until effective programs become available, healthcare professionals can use existing opportunities to involve CSHCN and parents in consultations (e.g., provide sufficient opportunities to ask questions).
Online verfügbar: 26. Januar 2024, Artikelversion: 15. März 2024
Gesehen am 23.01.2025